Multi-access, wireless and wired convergence architecture evolution and traffic scheduling mechanism - Shufeng SHI; Youyang YU (Dianxin kexue)
In 3GPP Rel-16, 3GPP 5G network architecture defines the wireless and wired converged architecture, that is, fixed and mobile converged network architecture, focusing on multiple valuable scenarios of this converged architecture, where the wired and wireless hybrid access scenario attracts much attention.The standard defines the multi-access traffic scheduling mechanism in this scenario.It was discussed in detail, including basic multi-access traffic scheduling mechanisms, enhanced the traffic splitting per packet mechanisms for UDP and Ethernet traffic flows for 5G-Advanced networks, and a new redundant transmission modes.In addition, 4G and 5G interworking scenarios were extended to support hybrid network traffic scheduling for 3GPP access to 5GC and non-3GPP access to EPC.